FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PEMBERIAN AIR SUSU IBU (ASI) EKSKLUSIF DI WILAYAH KERJA PUSKESMAS PEGANDAN KOTA SEMARANG - Setyorini, Ria Novita; Widjanarko, Bagoes; Sugihantono, Anung (Jurnal Kesehatan Masyarakat (Undip), 2017)
Exclusive breastfeeding can reduce infant mortality. However, based on reports from January to June 2016, exclusive breastfeeding coverage at Pegandan Health Center was only 7%. Therefore this research aimed to analyze the factors that influence the behavior of exclusive breastfeeding in the working area of Pegandan Health Center Semarang City.This was a quantitative with cross sectional approach research. The samples were using proportional sampling at mothers who had 7-12 months babies. Data were collected by interview using questionnaire. This research used univariate, bivariate, and multivariate analysis.The results of this research showed that majority of respondents aged 26-35 years, housewives and multiparous. 54.2% of respondents did not give exclusive breastfeeding. The chi-square test showed that knowledge (p=0.05) and attitudes toward exclusive breastfeeding (p=0,000) were significantly associated with exclusive breastfeeding. While age (p=0.151), job (p=0.356), parity (p=1,000), maternity place (p=0,723), birth attendant skill (p=0,616), exclusive breastfeeding information (p=0,055) availability of supporting facilities (p=0.638), husband (p=0.428), family (p=0.269), and significant others support (p=0.444) were not significantly associated with exclusive breastfeeding behavior. Binary logistic regression test results show that of all variables, only attitude has significant influence on exclusive breastfeeding behavior (OR = 7,299).It was suggested to optimize Breastfeeding Support Group and dissemination of information through social media as information delivery approaches.